The cost of care of systemic lupus erythematosus (SLE) in the UK: annual direct costs for adult SLE patients with active autoantibody-positive disease. (March 2014) - Khamashta, MA; Bruce, IN; Gordon, C; Isenberg, DA; Ateka-Barrutia, O; Gayed, M; Donatti, C; Guillermin, A-L; Foo, J; Perna, A
Objectives: The aim of the Systemic LUpus Erythematosus Cost of Care In Europe (LUCIE) study was to evaluate the annual direct medical costs of managing adults with active autoantibody-positive disease on medication for SLE in secondary care. This paper presents the UK analyses only. Methods: A cost-of-illness study was conducted from the perspective of the National Health Service. Health resource utilization data were retrieved over a two-year period from four centres in England and unit cost data were taken from published sources. Results: At baseline, 86 patients were included, 38 (44.2%) had severe SLE and 48 (55.8%) had non-severe SLE. The mean (SD) SELENA-SLEDAI score was 7.7 (5.7). The mean (SD) annual direct medical cost of was estimated at £3231 (£2333) per patient and was 2.2 times higher in patients with severe SLE compared with patients with non-severe SLE ( p < 0.001). Multivariate model analyses showed that renal disease involvement ( p = 0.0016) and severe flares ( p = 0.0001) were associated with higher annual direct costs. Conclusions: Improvement of the overall stability of SLE and early intervention to minimize the impact of renal disease may be two approaches to mitigate the long-term direct cost of managing SLE patients in the UK.